Insulation Failure and Externalized Conductor of a Single‐Coil Kentrox Lead: An Ongoing Story?. (12th November 2014) - BOGOSSIAN, HARILAOS; MIJIC, DEJAN; FROMMEYER, GERRIT; WINTER, JOACHIM
Externalized Conductor of a Single‐Coil Kentrox Lead Conductor externalization is a frequent complication with the St. Jude Medical Riata lead. Single case reports also reported externalization of conductors for dual‐coil Biotronik leads. Up to now, conductor externalization has not yet been reported for any single coil leads. We report for the first time an externalization of conductors in a Biotronik Kentrox single‐coil implantable cardioverter defibrillator (ICD) lead.